An analysis of the barriers and problems to web infrastructure development experienced by small businesses. (1st September 2004) - Boyes, James A.; Irani, Zahir
This paper documents and analyses current literature that considers the barriers and problems experienced by small businesses when attempting to use the World Wide Web for commercial gain. The paper provides a brief introduction describing the evolution of both the internet and World Wide Web. Similarly, the World Wide Web's potential value to the UK business community and UK economy is considered, and the advantages and benefits that become available to an organisation through the use of the web are discussed. The paper then notes that whilst the advantages offered to a Small Business through the use of the web are well documented, small businesses are often the most ill equipped organisations to capitalise upon them. The reasons for this centre upon the barriers and problems they encounter when they attempt to exploit the web for commercial gain. Consequently, a summary of the barriers they face, as documented within the literature is presented, and based upon its analysis a research agenda is proposed.